Beyond the norm: A case report and review on second trimester Cystic Hygroma with Hydrops Fetalis. - Samsudin, Suhaiza; Muniandy, Chitra; Che Yusof, Mohd Daud (2024)
A 33-year-old woman spontaneously conceived a foetus with cystic hygroma (CH) and underwent medical termination. The anomaly was detected early via routine ultrasound at a primary health clinic and subsequently referred to tertiary care. Due to financial constraints and the unacceptance of conceiving an abnormal foetus, the parents were not keen on genetic testing via amniocentesis or maternal serum, despite comprehensive genetic counselling by a Fetomaternal specialist. The prognosis of CH is poor and often related to chromosomal and major structural abnormalities. Undiagnosed CH before birth can lead to complications for the mother and foetus. Therefore, early ultrasonographic assessments, conducted by skilled personnel facilitate timely diagnosis. Clinicians must approach counselling with vigilance and take a holistic approach to addressing the patient’s factors in declining prenatal genetic screening. Given the possibility of a CH recurrence, offering prenatal genetic screening in future pregnancies is necessary. Therefore, ensuring the nationwide availability of these prenatal genetic screening tests at reduced costs is essential to make them accessible and affordable for all expectant mothers.